Exploring student's in-depth learning difficulties in mathematics through teachers' perspective - Ramli, Fatimah; Shafie, Norazzila; Ahmad Tarmizi, Rohani (Elsevier, 2013)
This study reports on a qualitative study of teachers teaching mathematics in a secondary school in Malaysia. The literature focuses on the role of teachers adopting in-depth approaches which lead to in-depth learning by students. Findings provide descriptions of factors that hinder in-depth learning of mathematics including student discipline, time constraints, and less exposure to the latest pedagogical techniques. Findings also provide teacher perspectives of pedagogical remedies that can help their students overcome the difficulties that hinder in-depth learning in secondary Mathematics classrooms such as fun learning, effective communication, problem based instruction, constructivism approach, real life application, technology integrated learning and student centred learning. Implications of the results of the study include describing a need for effort by teachers, schools, and the Ministry of Education to create and promote an environment conducive to in-depth learning in mathematics.